La comprensión de lectura y el mundo que me rodea (2019)
This article evidences the project carried out to strengthen reading comprehension through the application of seven research workshops based on theories related to reading, reading comprehension, artistic expressions, cultural identity, multiple intelligences, context and sociocultural theory. These theories seek to exploit the information about the environment that serves as a means for the development of this innovative didactic strategy that contributes to the improvement of educational processes of the eighth grade in the José Miguel Silva Plazas Technical Institute in the rural area of the Municipality of Duitama, Boyacá. By implementing the strategy, there was evident progress in some students regarding their role as participants of their cultural context. Their attitude towards reading comprehension was more critical, reflective, evaluative and creative; Students’ direct experiences with their environment, enhance learning processes, making this a significant process that enriches their integral formation.